Algal symbiont genera but not coral host genotypes correlate to stony coral tissue loss disease susceptibility among Orbicella faveolata colonies in South Florida - Klein, Allison M.; Sturm, Alexis B.; Eckert, Ryan J.; Walker, Brian K.; Neely, Karen L.; Voss, Joshua D. (Frontiers in Marine Science, 2024)
Stony coral tissue loss disease (SCTLD) has spread throughout the entirety of Florida’s Coral Reef (FCR) and across the Caribbean, impacting at least 30 coral species. The threatened hermatypic coral, Orbicella faveolata, demonstrates intraspecific variation in SCTLD affectedness with some colonies experiencing chronic disease lesions, while other nearby O. faveolata colonies appear unaffected with no disease signs over long monitoring periods. This study evaluated potential genotypic underpinnings of variable disease responses to SCTLD by monitoring and sampling 90 O. faveolata colonies from southeast Florida and the lower Florida Keys. High resolution analyses of >11,000 single nucleotide polymorphisms (SNPs) generated from 2bRAD sequencing indicated there were no SNP loci or genetic lineages significantly associated with O. faveolata SCTLD affectedness. Genotypic differences may still contribute to SCTLD susceptibility; however, these differences were not captured using this reduced representation sequencing approach. Algal symbiont community structure characterized from 2bRAD data revealed that the presence of Durusdinium spp. corresponded with SCTLD-affected colonies as compared to unaffected colonies, suggesting that algal symbiont community make-up may play some role in SCTLD resistance. Data generated by this study will be combined with complementary molecular and physiological approaches to further investigate the complex drivers of intraspecific SCTLD susceptibility and resilience.